2018
DOI: 10.1101/mcs.a002535
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of ERBB2-amplified colorectal cancer identifies potential mechanisms of resistance to targeted therapies: a report of two instructive cases

Abstract: ERBB2 amplification has been identified in ∼5% of KRAS wild-type colorectal cancers (CRCs). A recent clinical trial showed response to HER2-directed therapy in a subset of ERBB2-amplified metastatic CRCs resistant to chemotherapy and EGFR-directed therapy. With the aim of better understanding mechanisms of resistance to HER2-directed and EGFR-directed therapies, we report the complete molecular characterization of two cases of ERBB2-amplified CRC. PCR-free whole-genome sequencing was used to identify mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 49 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…With the aim of better understanding mechanisms of resistance to HER2-directed and EGFR-directed therapies, Owen et al reported the complete molecular characterization of these two cases of HER2 -amplified mCRC. Their findings included increased expression of MUC1 and MET , decreased expression of PTEN , and an activating mutation in PIK3CA [46]. These data support the hypothesis that a potentially promising alterative to overcome resistance mechanisms would be to apply a therapy in the upfront setting in order to suppress and ideally eradicate pre-existing resistant clones while they still are present in a low frequency subpopulation.…”
Section: Discussionmentioning
confidence: 71%
“…With the aim of better understanding mechanisms of resistance to HER2-directed and EGFR-directed therapies, Owen et al reported the complete molecular characterization of these two cases of HER2 -amplified mCRC. Their findings included increased expression of MUC1 and MET , decreased expression of PTEN , and an activating mutation in PIK3CA [46]. These data support the hypothesis that a potentially promising alterative to overcome resistance mechanisms would be to apply a therapy in the upfront setting in order to suppress and ideally eradicate pre-existing resistant clones while they still are present in a low frequency subpopulation.…”
Section: Discussionmentioning
confidence: 71%
“…Although HER2 blockade was remarkably effective, especially considering that the patients had received a median of five prior lines of treatment, most cases eventually relapsed, with a median progression-free survival (PFS) of 21 weeks (Sartore-Bianchi et al, 2016). How ERBB2-amplified gastrointestinal tumors that initially respond to HER2 blockade evolve during therapy and become resistant is largely unknown (Kim et al, 2018;Owen et al, 2018). Further knowledge is key to devising additional lines of treatment or mounting combinatorial preventive strategies.…”
Section: Significancementioning
confidence: 99%
“…This might be due to greater expression of the EpCAM tumour antigen in these cells, compared to HER2; however, this cannot be directly compared in this study due to the use of different antibodies. It was previously reported that in CRC EpCAM expression was up‐regulated by 100‐fold to 1000‐fold (Seeber et al ., 2016), while HER2 expression was up‐regulated by fivefold (Owen et al ., 2018) and 12‐fold (Blok et al ., 2013). Nevertheless, HER2 overexpression has been shown in patients with CRC (Ross and McKenna, 2001), and it has been suggested as a promising alternative therapeutic target (Ingold Heppner et al ., 2014; Greally et al ., 2018; Ross et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%